IMF Staff papers : Volume 24 No. 1. (IMF Staff Papers; IMF Staff Papers, 1977)
The purpose of the present study is to review these concepts and to estimate consistent series of potential output in manufacturing for Canada, the United States, Japan, France, the Federal Republic of Germany, Italy, the United Kingdom, and Sweden for the period 1955-1975. Potential output series are also projected for the medium term (1976-1978) based on forecasts of available resources. The production function method is selected as the best approach to derive potential output series. The function used in the paper is a modified Cobb-Douglas function that allows for economies of scale and cyclical variations in the intensity of use of employed labor and of the capital stock. The study concludes that the rate of growth of potential output in manufacturing is now lower in most industrial countries than it was in the late 1960s. However, the fall is not as large as is often claimed, so that the output gaps early in 1976 were extremely high in all the major industrial countries. The principal reasons for the slowdown in the rate of growth of potential output are the lower rate of capital accumulation and the reduction of the normal workweek, rather than the direct effect of the increase in the price of energy.